Antiproteinase 3 Positive Eosinophilic Granulomatosis with Polyangiitis Presenting with Heart Failure and Intraventricular Thrombosis. (29th January 2017) - Zhu, Dan; Luo, Yiming; Liu, Xiangyuan; Zu, Lingyun
Abstract : Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare systemic vasculitis commonly with cardiac complications. We describe a case of anti-PR3 ANCA-positive EGPA complicated by congestive heart failure and intraventricular thrombosis. Interestingly, the thrombus was resolved rapidly with steroid and cyclophosphamide in the setting of interrupted anticoagulation. To the best of our knowledge, we report the first case of anti-PR3 positive EGPA with extensive cardiac involvement. Our patient had overlapping features with previously studied ANCA-positive and ANCA-negative EGPA cases. We also hypothesize that the thrombogenic potential of eosinophils may play a central role in thrombogenesis in EGPA and aggressive immunosuppressive therapy remains the cornerstone of treatment, and the addition of anticoagulation therapy in the setting of thrombus formation and also very high risk of bleeding needs to be considered cautiously.